2020
DOI: 10.1037/trm0000214
|View full text |Cite
|
Sign up to set email alerts
|

From trauma to growth: The roles of event centrality, posttraumatic stress symptoms, and deliberate rumination.

Abstract: Researchers have increasingly found that traumatic events cannot only lead to pathological outcomes such as posttraumatic stress disorder (PTSD), but also to positive outcomes such as posttraumatic growth (PTG). Consistent with Tedeschi and Calhoun’s (2004) conceptual model of PTG, individuals must experience at least a moderate level of distress to experience growth. Moderate distress can also trigger deliberate rumination or meaning making, which can lead to PTG. Berntsen and Rubin (2006) have proposed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 67 publications
2
11
0
2
Order By: Relevance
“…Those who endorse lower maladaptive metacognitive beliefs, however, may be more likely to approach, rather than avoid, trauma-related thoughts and memories in an introspective manner that promotes meaning making (e.g., deliberative rumination rather than intrusive rumination; Cann et al, 2011). In fact, although cross-sectional in nature, some evidence suggests that when high centrality events are met with deliberate rumination, PTG is more likely to occur (Kramer et al, 2020). Therefore, lower metacognitive beliefs might allow for the development of PTG.…”
mentioning
confidence: 99%
“…Those who endorse lower maladaptive metacognitive beliefs, however, may be more likely to approach, rather than avoid, trauma-related thoughts and memories in an introspective manner that promotes meaning making (e.g., deliberative rumination rather than intrusive rumination; Cann et al, 2011). In fact, although cross-sectional in nature, some evidence suggests that when high centrality events are met with deliberate rumination, PTG is more likely to occur (Kramer et al, 2020). Therefore, lower metacognitive beliefs might allow for the development of PTG.…”
mentioning
confidence: 99%
“…On the other hand, trauma centrality can play a significant role in posttraumatic growth (PTG; Tedeschi et al., 2018). Existing evidence shows that trauma centrality is correlated with PTG (Barton et al., 2013; Boals & Schuettler, 2011; Kramer et al., 2019). For example, in a sample of trauma‐exposed undergraduates, Groleau et al.…”
Section: Sample Study Methodsmentioning
confidence: 99%
“…When a traumatic event becomes a core component of self-identity, it may be causally related to internal, stable, and global depressive attributions (Berntsen & Rubin, 2007). Trauma centrality can act as a key factor in posttraumatic stress disorder (PTSD; Berntsen & Rubin, 2007), and it has been consistently correlated with posttraumatic stress symptoms (PTSS; Barton et al, 2013;Bernard et al, 2015;Boals & Schuettler, 2011;Kramer et al, 2019). In a sample of veterans, Brown et al (2010) found that after controlling for depressive symptoms, trauma centrality uniquely contributed to PTSS; Vermeulen et al (2019) found similar results among trauma-exposed undergraduates.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…) 。 代 表 的 な も の と し て, ト ラ ウ マ 後 成 長 (posttraumatic growth) , 出 来 事 に 関 す る 反 す う (event-related rumination) , 抑 う つ(depression) が 挙 げられる。トラウマ後成長とは,強いストレスを感じ る出来事やトラウマ的な出来事の後に報告されるポジ ティブな変化のことである (Tedeschi & Calhoun, 1996;Tedeschi, Cann, Taku, Senol-Durak, & Calhoun, 2017) 。 CES とトラウマ後成長の相関は,トラウマが個人の アイデンティティに重大な影響を与え,それを契機に 人生に対して,あるいは自己,他者,世界に対しての 捉え直しが生じていることを意味する。出来事に関す る反すうとは,出来事を経験した後にその出来事につ いて,意図的あるいは無意図的に,繰り返し考える程 度を指す (Cann et al, 2011) 。CES とトラウマ的な出 来事に関する反すうの相関は,出来事の中心性の高さ とその出来事について考える程度の関連を表す。抑う つおよび大うつ病は PTSD に併存しやすい精神疾患で ある (OʼDonnell, Creamer, & Pattison, 2004) 。CES と抑 うつの相関は,トラウマ的な出来事の自己にとっての 中心性の高さが抑うつの高さと関連することを表す。 さらに,CES は PTSS を縦断的に予測することが示 さ れ て い る (Boals & Ruggero, 2016) (Berntsen & Rubin, 2006) ,原版および各国で作成された翻訳版の モデル適合度が不十分であることが指摘されている (Eğeci & Doğruyol, 2019;Ionio, Mascheroni, & Di Blasio, 2018;Vermeulen et al, 2020) (Allebaugh, 2013;Brooks, Graham-Kevan, Lowe, & Robinson, 2017;Groleau, Calhoun, Cann, & Tedeschi, 2013;Kramer, Whiteman, Witte, Silverstein, & Weathers, 2020;Lancaster, Klein, Nadia, Szabo, & Mogerman, 2015)…”
unclassified